Estimating a small-scale macroeconometric model (SSMM) for Nigeria : a dynamic stochastic general equilibrium (DSGE) approach - Mordi, Charles N. O.; Central Bank of Nigeria, Research Department; Adebiyi, Michael A.; Central Bank of Nigeria (Abuja, Nigeria Central Bank of Nigeria, 2010)
Attempts to develop a small-scale macroeconometric model for the Nigerian economy using the dynamic stochastic general equilibrium (DSGE) methodology.
Includes bibliographical references.
oif 16/05/17
Ref.
Keywords: Econometric modeling; Econometrics; Macroeconomics; Nigeria